Analysis of the integration of the hot-lab method in resistor practical work using incandescent lamps on the topic of conductor resistance with PhET virtual lab - Mulhayatiah, Diah; Rachman, Muhammad Ziddan; Malik, Adam; Agustina, Rena Denya; Chusni, Muhammad Minan; Yuningsih, Endah Kurnia (Journal of Environment and Sustainability Education, 2025)
In the digital era, students still face difficulties in understanding abstract physics concepts such as Ohm's Law and resistance, primarily due to conventional, teacher-centered instructional methods. This study aims to investigate the integration of the Higher-Order Thinking Laboratory (HOT-Lab) method with PhET virtual simulations to improve students’ higher-order thinking skills (HOTS) in learning about conductor resistance. Using an experimental method, students conducted virtual practicum activities via the PhET Interactive Simulations platform, specifically utilizing the "DC Circuit Construction Kit." The learning process followed structured HOT-Lab phases: identifying problems, hypothesis formulation, experimentation, data analysis, and result communication. Results showed a strong linear correlation (R² = 0.9999) between voltage and electric current, indicating that incandescent lamps can function as resistors under certain conditions, consistent with Ohm’s Law. Regression analysis further validated this with a model  ????=0.0554????+0.0021, and students demonstrated improved conceptual understanding and analytical reasoning. The integration of HOT-Lab with virtual labs is applicable in remote or resource-limited learning environments, promoting active, reflective, and student-centered learning aligned with 21st-century skills.